Culturing and Multiplexed Time‐Lapse Imaging of Fungal Isolates from Marine and Coastal Environments. Issue 4 (2nd April 2021) - Mitchison‐Field, Lorna M. Y.; Gladfelter, Amy S.
Abstract: Fungi play a crucial role in biogeochemical cycling and shaping biological communities at macro‐ and microcosmic scales. However, fungi have been largely overlooked in studies of marine ecology and microbiology. Here we present protocols for preparing culture media, collecting and culturing fungi from several types of marine environments and animal hosts, and preparing microscopy slides for long‐term time lapse imaging of fungal isolates. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Solid media preparation Alternate Protocol 1 : Liquid media preparation Basic Protocol 2 : Sample collection and plating from ocean water Alternate Protocol 2 : Sample collection and plating from coastal sediment Alternate Protocol 3 : Sample collection and plating from animal holobionts Support Protocol 1 : Making frozen stocks Support Protocol 2 : Streaking cultures from frozen stocks Basic Protocol 3 : Slide preparation and assembly for imaging © 2021 by John Wiley & Sons, Inc.